Social democracy and the monetary union (New York, 2001)
"Since the late 1960s social democrats have become the dominant political force in the European Union. In fact, Social Democrats govern in no less than 11 of the 15 member states. Simultaneously, the EU has embarked on its most far-reaching project yet, namely Economic and Monetary Union (EMU); a project that was designed mainly by non-Social Democratic governments. This volume provides the first in-depth and comparative analysis of the views and policies of nine European Social Democratic parties concerning economic governance under Europe's new single currency and of the impact of the new political and institutional constellation in the EU on the process of economic integration and European social democracy."